Application of HPCCC Combined with Polymeric Resins and HPLC for the Separation of Cyclic Lipopeptides Muscotoxins A⁻C and Their Antimicrobial Activity - Cheel, José; Hájek, Jan; Kuzma, Marek; Saurav, Kumar; Smýkalová, Iva; Ondráčková, Eliška; Urajová, Petra; Vu, Dai Long; Faure, Karine; Kopecký, Jiří; Hrouzek, Pavel (Molecules, 2018)
Muscotoxins are cyanobacterial cyclic lipopeptides with potential applications in biomedicine and biotechnology. In this study, Desmonostoc muscorum CCALA125 strain extracts were enriched by polymeric resin treatment, and subjected to HPCCC affording three cyclic lipopeptides (1⁻3), which were further repurified by semi-preparative HPLC, affording 1, 2, and 3, with a purity of 86%, 92%, and 90%, respectively. The chemical identities of 2⁻3 were determined as muscotoxins A and B, respectively, by comparison with previously reported ESI-HRMS/MS data, whereas 1 was determined as a novel muscotoxin variant (muscotoxin C) using NMR and ESI-HRMS/MS data. Owing to the high yield (50 mg), compound 2 was broadly screened for its antimicrobial potential exhibiting a strong antifungal activity against Alternaria alternata, Monographella cucumerina, and Aspergillus fumigatus, with minimum inhibitory concentration (MIC) values of 0.58, 2.34, and 2.34 µg/mL; respectively, and weak antibacterial activity against Bacillus subtilis with a MIC value of 37.5 µg/mL. Compounds 1 and 3 were tested only against the plant pathogenic fungus Sclerotinia sclerotiorum due to their low yield, displaying a moderate antifungal activity. The developed chromatographic method proved to be an efficient tool for obtaining muscotoxins with potent antifungal properties.
Keywords: Bacillus subtilis; Cyanobacteria; Lipopeptides; Resins, Synthetic; vysokoúčinná kapalinová chromatografie; molekulární struktura; Molecular Structure; Microbial Sensitivity Tests; sinice; Anti-Infective Agents; Chromatography, High Pressure Liquid; Peptides, Cyclic; syntetické pryskyřice; mikrobiální testy citlivosti; Ascomycota; Bacterial Toxins; lipopeptidy; cyklické peptidy; antiinfekční látky; bakteriální toxiny